2000
DOI: 10.1210/endo.141.10.7711
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone: A Mediator of Myocardial Necrosis and Renal Arteriopathy*

Abstract: To determine the role of aldosterone in mediating cardiovascular damage, we performed ablation/replacement experiments with aldosterone in a rat model of cardiac injury. Administration of angiotensin II and Nomega-nitro-L-arginine methyl ester (L-NAME; nitric oxide synthesis inhibitor) to male rats drinking 1% saline caused hypertension, severe biventricular myocardial necrosis, proteinuria, and fibrinoid necrosis of renal and cardiac vessels. Removal of aldosterone by adrenalectomy or through administration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
91
1
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 349 publications
(102 citation statements)
references
References 32 publications
4
91
1
4
Order By: Relevance
“…14 Likewise, in the stroke-prone hypertensive rat on a high sodium intake, aldosterone infusion during ACE inhibition with captopril was associated with proteinuria and malignant nephrosclerosis, 15 whereas in a hypertensive rat model subjected to angiotensin II and N-nitro-L-arginine methyl ester (L-NAME) infusion, renal and cardiac damage was prevented by aldosterone removal through adrenalectomy or administration of eplerenone. 13 Moreover, in the streptozotocin-induced diabetic rat with increased renal protein excretion, administration of spironolactone markedly attenuated urinary protein excretion and prevented early renal injury, indirectly indicating involvement of aldosterone in this process of renal injury. 16 Similar findings were obtained in the streptozotocin-induced diabetic rat and the db/db (a rodent model of type 1 diabetes) mouse when eplerenone was used as a mineralocorticoid receptor antagonist.…”
Section: Aldosterone and Nephropathymentioning
confidence: 91%
See 3 more Smart Citations
“…14 Likewise, in the stroke-prone hypertensive rat on a high sodium intake, aldosterone infusion during ACE inhibition with captopril was associated with proteinuria and malignant nephrosclerosis, 15 whereas in a hypertensive rat model subjected to angiotensin II and N-nitro-L-arginine methyl ester (L-NAME) infusion, renal and cardiac damage was prevented by aldosterone removal through adrenalectomy or administration of eplerenone. 13 Moreover, in the streptozotocin-induced diabetic rat with increased renal protein excretion, administration of spironolactone markedly attenuated urinary protein excretion and prevented early renal injury, indirectly indicating involvement of aldosterone in this process of renal injury. 16 Similar findings were obtained in the streptozotocin-induced diabetic rat and the db/db (a rodent model of type 1 diabetes) mouse when eplerenone was used as a mineralocorticoid receptor antagonist.…”
Section: Aldosterone and Nephropathymentioning
confidence: 91%
“…Experimental studies suggest the involvement of both mechanisms. 12,13,[30][31][32] In a study reported by Dworkin et al, haemodynamic factors were responsible for the glomerular injury in rats with deoxycorticosterone-salt-induced hypertension. 32 Sechi et al.…”
Section: Mechanism Of Antiproteinuric Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known to regulate a number of pathophysiological pathways important to post‐MI HF, including inhibition of nitric oxide activity,10 acute endothelial dysfunction,11 increased vascular tone,12 vascular smooth muscle cell and cardiomyocyte necrosis,13, 14 myocardial hypertrophy and fibrosis,15, 16 apoptosis,17 and unfavorable LV remodeling 18. Consequently, a number of landmark clinical studies have highlighted the significant benefits of aldosterone antagonist therapy on clinical outcomes post‐MI 19, 20, 21…”
Section: Introductionmentioning
confidence: 99%